SURVEY OF AEDES AEGYPTI LARVAE ON THE PERIMETER OF THE AREA AT THE PORT OF GORONTALO CITY - Ekawaty Prasetya; Zul Fikar Ahmad (International Journal of Health Science & Medical Research, 2022)
The port is a meeting point where the ships, goods and people embark and disembark, also a gateway for the transformation of the spread of diseases such as dengue fever. The efforts to prevent dengue transmission at ports are to free the port area from the life of the Aedes aegypti mosquito. At the perimeter of the port area of   Gorontalo, the HI and CI gures for 2011-2013 have exceeded the predetermined indicator, namely 0 and at the port, there are many buildings and containers for port activities that can become breeding grounds for larvae. The formulation of the problem in this study is how the results of the Aedes aegypti larva survey in the Perimeter Area in the Port of Gorontalo City are. The novelty of this study is due to research on surveys of Aedes Aegypti larvae around the area in the port . This study aimed to determine the HI and CI numbers and the types of potential breeding sites for Aedes aegypti larvae in the perimeter area of   the port of Gorontalo city. This research was an observational study with a descriptive study approach. Where the samples studied were 25 buildings and 48 containers. The sampling technique used was total sampling. Based on the results of data analysis, it is known that the HI and CI numbers on the perimeter area in the port of Gorontalo city are HI (16%) and CI (12.5%) and the type of potential breeding place for Aedes aegypti larvae are buckets. For this reason, it is hoped that the port of Gorontalo City will close and drain the TPA and the Class III KKP of Gorontalo further to improve the control of Aedes aegypti larvae and mosquitoes.Keywords: Larvae survey; Port; Aedes aegypti